Thallium isotopic evidence for ferromanganese sediments in the mantle source of Hawaiian basalts - Nielsen, Sune G.; Rehkämper, Mark; Norman, Marc D.; Halliday, Alex N.; Harrison, Darrell (Nature, 2006)
Ocean island basalts are generally thought to be the surface expression of mantle plumes, but the nature of the components in the source regions of such mantle plumes is a subject of long-standing debate. The lavas erupted at Hawaii have attracted particular attention, as it has been proposed that coupled 186 Os and 187 Os anomalies reflect interaction with the Earth's metallic core 1 , 2 . It has recently been suggested, however, that such variations could also result from addition of oceanic ferromanganese sediments to the mantle source of these lavas 3 , 4 , 5 . Here we show that Hawaiian picrites with osmium isotope anomalies also exhibit pronounced thallium isotope variations, which are coupled with caesium/thallium ratios that extend to values much lower than commonly observed for mantle-derived rocks. This correlation cannot be created by admixing of core material, and is best explained by the addition of ferromanganese sediments into the Hawaii mantle source region. However, the lack of correlation between thallium and osmium isotopes and the high thallium/osmium ratios of ferromanganese sediments preclude a sedimentary origin for the osmium isotope anomalies, and leaves core–mantle interaction as a viable explanation for the osmium isotope variations of the Hawaiian picrites.